Microstructure and corrosion behavior of Zn-Co alloys deposited from three different plating baths - Bajat Jelena B.; Stevanović Sanja I.; Jokić Bojan M. (Journal of the Serbian Chemical Society, 2011)
The effects of plating baths of different composition on the microstructure and corrosion stability of Zn-Co alloy coatings were studied. Zn-Co alloys with the same Co content were deposited from chloride plating baths containing different amounts of Co2+ ions, as well as from a sulphate-chloride plating bath. The surface morphology and crystallite size were investigated by scanning electron microscopy (SEM) and atomic force microscopy (AFM). The corrosion stability of the Zn- Co alloys was determined by following the change of the open circuit potential with time of immersion in a 3 % NaCl solution and by polarization measurements. The results showed a significant influence of the plating bath on the morphology and corrosion stability of the Zn-Co alloys. The surface of the alloy coatings deposited from the chloride baths were uniform and homogenous, whereas the deposit obtained from the sulphate-chloride bath was quite inhomogeneous. The corrosion stability of the homogenous Zn-Co deposits obtained by deposition from both chloride baths was higher than that of the deposit obtained from the sulphate-chloride bath. An increase in the Co content in the chlorideplating bath resulted in a reduction of the alloy crystallite size and it was shown that the alloy with the smaller crystallites of the two alloy deposits, although having the same chemical content, exhibited a lower corrosion rate.